The Correlation Between Mathematics Learning Independence And Computational Thinking Ability Of Elementary School Students - Cahya, Arinta Nilam; Prananto, Irfan Wahyu (Jurnal Pendidikan Tambusai, 2024)
Independence in learning mathematics is an important thing for every student to have so that students have good computational thinking skills. This study aims to determine the relationship between math learning independence and computational thinking skills of fifth grade students of SD Negeri Wotan 02 Pati. This research is a quantitative research with correlation research type. The research was conducted in grades VA and VB of SD Negeri Wotan 02 Pati involving 41 students as samples. Data collection was carried out using a math learning independence scale adopted in Pamungkas Tubagus's research (2022) and computational thinking ability test questions adapting to the bebras challenge. Data analysis technique using product moment correlation technique. Based on the results of the study, the variables of mathematics learning independence and students' computational thinking ability have a significance value of 0.000 with a correlation coefficient of 0.784. It shows that both variables of math learning independence and computational thinking ability have a significant and positive relationship, with a strong level of relationship category. Therefore, students are advised to increase their independence in learning mathematics so that their computational thinking ability also increases.